The role of extracranial carotid duplex in predicting functional outcome in first time lacunae strokes. (3rd April 2023) - Jiang, Ting-Wei; Hsu, Ying-Lin; Yang, Ju-Lan; Shih, Yin-Tzer; Lin, Chih-Ming
ABSTRACT: Background: Stroke is the third largest cause of death both worldwide and in Taiwan. Among the various stroke subtypes, lacunae strokes account for 20 to 30% of the total stroke population. Through vigorous risk control factors, the effective prevention and the long-term functional outcome remains are yet to be investigated. Carotid duplex is a non-invasive neuroimaging modality that is routinely applied to stroke patients. In the current research, we correlate baseline carotid duplex examination parameters with functional outcome assessment in an attempt to ascertain important variables for early outcome prediction. Method: We retrospectively recruited lacunae ischemic stroke patients from the Department of Neurology, Changhua Christian Hospital. Patient baseline demographics, biochemistry, neuroimaging, and outcome assessments were thoroughly evaluated via a modified Rankin Scale (mRS), NIHSS, and Barthel index scores, both prior and subsequent to patient discharge for a period of up to one year. Patients were divided into two groups based on their functional recovery status. This current study utilizes the Kaplan–Meier method to draw the survival curve and adopts the Cox proportional hazards model to estimate the hazard ratio between the two groups. The risk modeling method is also applied to formulate the best fit in seeking and identifying the variables, which has the most impact on determining theoutcome predictor. All statistical analyses were performed using R for Windows (version 3.6.3), with p < 0.05 meaning statistical significance and 0.05 <  p < 0.1 denoting marginal statistical significance. Results: One hundred forty-one ischemic lacunae stroke patients are included in the study, of which the follow-ups of 69 patients showed no physical functionality improvement, whereas 72 patients demonstrated favorable functional outcomes. In terms of underlying diseases, more than 80% of the patients suffered from hyperlipidemia upon hospitalization and more than 40% of the patients suffered from diabetes mellitus and heart disease. There was a significant difference in pulmonary disease between improvement and non-improvement in disability (1.4% vs 10.1%, p = 0.034). The average age of the improved group was lower than that of the non-improved group (65.5 vs. 72, p = 0.014), and the WBC was higher (8 vs 6.95, p = 0.005); furthermore, higher NIHSS scores (6.5 vs 3, p = 0.001) and lower Barthel index scores (47.5 vs 80, p < 0.001) were also noted. The group with improved mRS required a longer hospital stay (with a median of 10 days), while their un-improved counterpart required 8 days ( p < 0.05). The majority of patients were discharged within 30 days, and there was a slight difference between the two survival curves (marginal statistical significance, 0.05 <  p < 0.1). The hazard ratio of the improved group was 0.7188. There was a difference in the end diastolic velocity (EDV) of common carotid artery (CCA) between the lesion and non-lesion sides of the patients ( p < 0.05). Risk-stratifying models indicate that diabetes mellitus, peak systolic velocity (PSV) of the internal carotid artery (ICA) on the lesion side, the diameter of the ICA on the non-lesion side, and the pulsatility index (PI) of the ICA and external carotid artery (ECA) were selected as the most important factors affecting the end diastolic velocity (EDV) of the common carotid artery (CCA) in all four models. Conclusion: In the current study, the most suitable length of stay in hospital for lacunae stroke patients to fully recuperate is ten days. Additionally, CCA EDV might be the key determinant, with baseline diabetes mellitus acting in a medium role, capable of altering long-term outcome functionality and recovery.